Multi-Keyword Ranked Searchable Encryption with the Wildcard Keyword for Data Sharing in Cloud Computing. (11th October 2021) - Liu, Jinlu; Zhao, Bo; Qin, Jing; Zhang, Xi; Ma, Jixin
Abstract: Multi-keyword ranked searchable encryption (MRSE) supports multi-keyword contained in one query and returns the top-k search results related to the query keyword set. It realized effective search on encrypted data. Most previous works about MRSE can only make the complete keyword search and rank on the server-side. However, with more practice, users may not be able to express some keywords completely when searching. Server-side ranking increases the possibilities of the server inferring some keywords queried, leading to the leakage of the user's sensitive information. In this paper, we propose a new MRSE system named 'multi-keyword ranked searchable encryption with the wildcard keyword (MRSW)'. It allows the query keyword set to contain a wildcard keyword by using Bloom filter (BF). Using hierarchical clustering algorithm, a clustering Bloom filter tree (CBF-Tree) is constructed, which improves the efficiency of wildcard search. By constructing a modified inverted index (MII) table on the basis of the term frequency-inverse document frequency (TF-IDF) rule, the ranking function of MRSW is performed by the user. MRSW is proved secure under adaptive chosen-keyword attack (CKA2) model, and experiments on a real data set from the web of science indicate that MRSW is efficient and practical.